A method of large DNA fragment enrichment for nanopore sequencing in region 22q11.2 - Lei, Yu-Qing; Xu, Liang-Pu; Cao, Hua; Wang, Xin-Rui (Frontiers in Genetics, 2022)
Background: 22q11.2 deletion syndrome (22q11.2DS) is a disorder caused by a small part of chromosome 22 missing. The current diagnosis is established by the identification of a heterozygous deletion at chromosome 22q11.2 on chromosomal microarray analysis or other genomic analyses. However, accurate identification of the breakpoint contributes to a clearer understanding of the 22q11.2 deletion syndrome. Methods: In this study, we present a feasible nanopore sequencing method of 22q11.2 deletion. This DNA enrichment method, region-specific amplification (RSA), is able to analyze the 22q11.2 deletion by specific amplification of approximately 1 Mb region where the breakpoint might exist. RSA introduces universal primers into the target region DNA by a Y-shaped adaptor ligation and a single primer extension. The enriched products, completed by amplification with universal primers, are then processed by standard ONT Ligation Sequencing protocols. Results: RSA is able to deliver adequate coverage (>98%) and comparable long reads (average length > 1 Kb) throughout the 22q11.2 region. The long Nanopore sequencing reads, derived from three umbilical cord blood samples, have facilitated the breakpoint finding of the 22q11.2 deletion, as well as by sanger sequencing. Conclusions: The Oxford Nanopore MinION sequencer can use RSA to sequence the target region 22q11.2; this method could also be used for other hard-to-sequence parts of the genome.